Multiple solutions of boundary value problems on time scales for a φ-Laplacian operator - Amster, Pablo Gustavo (2020)
We establish the existence and multiplicity of solutions for some boundary value problems on time scales with a ϕ-Laplacian operator. For this purpose, we employ the concept of lower and upper solutions and the Leray–Schauder degree. The results extend and improve known results for analogous problems with discrete p-Laplacian as well as those for boundary value problems on time scales.